Health-Related Quality of Life for Patients Receiving Tumor Treating Fields for Glioblastoma - Palmer, Joshua D.; Chavez, Gordon; Furnback, Wesley; Chuang, Po-Ya; Wang, Bruce; Proescholdt, Christina; Tang, Chao-Hsiun (Frontiers in Oncology, 2021)
BACKGROUND: To date there has been no large-scale, real-world study of health-related quality of life outcomes for patients using Tumor Treating Fields (TTFields) therapy for glioblastoma (GBM) treatment. METHODS: A survey was mailed to 2,815 patients actively using TTFields for treatment of GBM in the US (n=2,182) and Europe (n=633). The survey included patient-reported demographic and clinical information as well as EuroQol’s EQ-5D-5L and Visual Analogue Scale (EQ-VAS) overall health score. RESULTS: 1,106 applicable patients responded to the survey (782 US, 324 Europe) with a mean age of 58.6 years (SD=12.3). Average time since diagnosis and time using TTFields were 21.5 months (SD=25.1) and 13.5 months (SD=13.2) respectively. Over 61% of patients had been diagnosed at least 1 year prior, 28.4% at least 2 years prior and 45 patients (4.2%) had been diagnosed at least 5 years prior. Progressed disease was reported in 307 patients while 690 reported non-progressed disease. Regression analyses showed that GBM disease progression and older age had predictable negative associations (p<.001) with most EQ-5D-5L dimensions and the EQ-VAS. However, longer time since diagnosis was associated with improved self-care (p<.05), usual activity (p<.01), and EQ-VAS (p<.05) overall and in patients with progressed disease (p<.01, .05, .01 respectively). Additionally, longer time using TTFields was associated with improved mobility (p<0.05), self-care (p<.001), usual activity (p<0.01), and EQ-VAS (p<0.01) overall, with improved EQ-VAS in progression-free patients (p<.05), and with improved mobility (p<.05), self-care (p<.01), usual activity (p<.05), and EQ-VAS (p<.05) in patients with progressed disease. CONCLUSION: This is the largest real-world study of patient-reported quality of life in GBM and TTFields treatment to date. It shows unsurprising negative associations between quality of life and disease progression and older age as well as more novel, positive associations between quality of life and longer time since diagnosis and time using TTFields therapy.